2011
DOI: 10.1016/j.jlumin.2010.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent properties of Eu2+ and Ce3+ ions in strontium litho-silicate Li2SrSiO4

Abstract: a b s t r a c tThe luminescent properties of Eu 2 + and Ce 3 + ions in Li 2 SrSiO 4 have been studied upon excitation in the 2-20 eV region. Based on the results of luminescent measurements, values of the crystal field splitting and the centroid shift of the Ce 3 + 5d configuration in Li 2 SrSiO 4 were found and compared with those of Ce 3 + ions in some other inorganic compounds. The Eu 2 + ions in Li 2 SrSiO 4 exhibit a broad band emission with a maximum at 576 nm, which is due to the 4f 6 5d-4f 7 transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…Because the luminescence excitation spectrum of Ce 3+ in this compound exhibits a similar band, it can be assigned to absorption of excitation energy by the BaLi 2 SiO 4 crystal lattice. In this instance it can be concluded that the optical absorption edge for BaLi 2 SiO 4 was shifted to lower energies compared with CaLi 2 SiO 4 (7.15 eV at 10 K [15]) and SrLi 2 SiO 4 (6.85 eV at 10 K [8]). The observed shift may be due to involvement of AE states (Ba 6s) in electronic transitions near the BaLi 2 SiO 4 fundamental absorption edge.…”
Section: Introductionmentioning
confidence: 73%
See 4 more Smart Citations
“…Because the luminescence excitation spectrum of Ce 3+ in this compound exhibits a similar band, it can be assigned to absorption of excitation energy by the BaLi 2 SiO 4 crystal lattice. In this instance it can be concluded that the optical absorption edge for BaLi 2 SiO 4 was shifted to lower energies compared with CaLi 2 SiO 4 (7.15 eV at 10 K [15]) and SrLi 2 SiO 4 (6.85 eV at 10 K [8]). The observed shift may be due to involvement of AE states (Ba 6s) in electronic transitions near the BaLi 2 SiO 4 fundamental absorption edge.…”
Section: Introductionmentioning
confidence: 73%
“…It can be concluded that stabilization of Eu 2+ in MLi 2 SiO 4 requires the use of a reducing agent in the synthesis. at 525 nm [8]. The luminescence excitation spectrum of Eu 2+ in BaLi 2 SiO 4 was different.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations